Molding material
A cellulose fiber and urethane fiber-based molding material with a resin and crosslinking agent addresses fiber detachment and dust issues, ensuring strength and environmental sustainability.
Patent Information
- Application Number
- JP2023107973
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Conventional molding materials containing cellulose fibers and resin suffer from fiber detachment and dust generation during repeated molding processes, particularly when exposed to heat, which affects the strength and suitability for applications like fluid flow paths and ink cartridges.
A molding material comprising cellulose fibers, a binder, and urethane fibers, with a resin having specific molecular weight distribution characteristics and a crosslinking agent, which enhances compatibility and suppresses dust generation even under thermal stress.
The material effectively prevents fiber detachment and dust generation, maintaining strength and suitability for diverse environments, while promoting recyclability and reducing environmental impact.
Smart Images

Figure 2025006922000001 
Figure 2025006922000002 
Figure 2025006922000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a molding material. [Background technology]
[0002] Conventionally, molded articles manufactured using materials containing cellulose fibers and resins have been known. For example, Patent Document 1 proposes a cellulose fiber-reinforced thermoplastic resin molded article containing a thermoplastic resin, cellulose fibers, and organic fibers different from the cellulose fibers, with the aim of providing a molded article that has both a sufficiently high bending modulus (rigidity) and excellent impact strength. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 7097521 Summary of the Invention [Problem to be solved by the invention]
[0004] However, with the materials of the prior art, when there is a thermal history of molding, for example when a molded product or gate material used during molding is melted and pelletized, and then molded again, fibers can fall off and generate dust. [Means for solving the problem]
[0005] One aspect of the molding material according to the present invention is A molding material comprising cellulose fibers and a resin, The resin includes a binder and a urethane fiber, The resin has a molecular weight distribution curve measured by a GPC method using chloroform as an eluent, in which a maximum value 1 is present at a weight average molecular weight of 50,000 to 150,000 and a maximum value 2 is present at a weight average molecular weight of 75,000 to 300,000, The area value at the local maximum value 2 is smaller than the area value at the local maximum value 1. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 1). [Diagram 2] FIG. 2 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 2). [Diagram 3] FIG. 3 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, an embodiment of the present invention will be described. The embodiment described below is an example of the present invention. The present invention is not limited to the following embodiment, and includes various modified forms that are implemented within the scope that does not change the gist of the present invention. Note that not all of the configurations described below are necessarily essential configurations of the present invention.
[0008] 1.Molding materials A molding material according to one embodiment of the present invention is a molding material comprising cellulose fibers and a resin, the resin comprising a binder and urethane fibers, and a molecular weight distribution curve of the resin measured by a GPC method using chloroform as an eluent, the molecular weight distribution curve having a maximum value 1 at a weight average molecular weight of 50,000 to 150,000 and a maximum value 2 at a weight average molecular weight of 75,000 to 300,000, the area value at maximum value 2 being smaller than the area value at maximum value 1.
[0009] In a cellulose fiber-reinforced thermoplastic resin molded product containing a thermoplastic resin, cellulose fibers, and organic fibers different from the cellulose fibers, there is a problem that fibers tend to fall off significantly from the molded product, making the product unsuitable for use in environments where dust generation and the like is a problem, such as components having fluid flow paths or components arranged around such components, ink cartridges, various containers, and various fixtures.
[0010] It has now been discovered that a molding material containing cellulose fibers, a binder, and urethane fibers can be suitably used for producing molded bodies that contain cellulose fibers, have excellent impact strength and flexural strength, and have reduced dust generation.
[0011] It is believed that such an effect is obtained for the following reasons. That is, by containing cellulose and binders having high theoretical strength and excellent shape retention, and also containing urethane having excellent compatibility and affinity with cellulose fibers and binders, it is possible to prevent and suppress the functions of these components from being offset, and to fully exhibit the functions of these components. More specifically, during the production of a molded body using a molding material, or in a molded body produced using a molding material, it is possible to increase the wettability of the binder with respect to the cellulose fibers while fully exhibiting the functions of the cellulose fibers and binders, and it is possible to suitably prevent and suppress interfacial peeling between different components constituting the molded body. As a result, it is believed that the above-mentioned effects are obtained. In addition, since it is possible to suitably prevent and suppress interfacial peeling between different components constituting the molded body, it is possible to obtain a molded body in which problems such as dust generation are effectively prevented.
[0012] Furthermore, by containing cellulose fibers, which are abundant natural materials derived from plants, it is possible to appropriately address environmental issues and save buried resources, etc., and it is also advantageous from the viewpoints of stable supply of molding materials and molded articles produced using the same, cost reduction, etc. Furthermore, cellulose fibers are a component that is contained in large amounts not only in virgin pulp but also in waste paper, old cloth, etc., and it is also advantageous from the viewpoint of promoting effective reuse of resources.
[0013] Furthermore, although urethane fibers are found in large quantities in waste clothing and the like, when they are mixed with other components, such as in blended textiles, they are difficult to isolate from the other components. In addition, they generate toxic gases when thermally processed at 200°C or above, making them difficult to reuse and difficult to incinerate in the past. However, according to the present invention, urethane fibers contained in waste clothing and the like can be suitably reused.
[0014] On the other hand, if the above conditions are not satisfied, satisfactory results cannot be obtained. For example, even if the material contains cellulose fibers and a binder, if it does not contain urethane, the wettability of the binder to the cellulose fibers cannot be sufficiently excellent, and in the molded body produced using the molding material, interfacial peeling between different components is likely to occur, and the strength of the molded body cannot be sufficiently excellent. In addition, the molded body produced using the molding material is likely to have a problem of dust generation.
[0015] Furthermore, even if the material contains cellulose fibers and urethane fibers, if it does not contain a binder, the moldability of the molded article will be significantly reduced, making it difficult to manufacture the molded article itself.
[0016] Furthermore, even if a molding material contains a binder and urethane fibers, if it does not contain cellulose fibers, the effects of containing cellulose fibers as described above will not be achieved, and the strength of the molded body produced using the molding material will be significantly low.
[0017] On the other hand, when there is a molding thermal history, such as when a molded product or a gate material used during molding is melted and pelletized, and then molded again, the resin in the molding material will deteriorate due to thermal decomposition. In particular, low-melting resins that melt at less than 200°C are prone to thermal decomposition. Furthermore, when there is a molding thermal history, fiber loss from the molded product becomes more noticeable, making it difficult to suppress dust generation.
[0018] Therefore, the inventors conducted extensive research and found that, when a resin containing a binder and urethane fibers has an appropriate amount of high molecular weight components, dust generation can be effectively suppressed even when there is a molding thermal history.
[0019] The various raw materials contained in the molding material will be described below.
[0020] 1.1 Cellulosic fibers The molding material according to this embodiment contains cellulose fibers.
[0021] The cellulose fibers are a component that greatly contributes to maintaining the shape of a molded article produced using the molding material according to this embodiment, and also has a significant effect on the properties of the molded article, such as its strength.
[0022] Cellulose is a plant-derived, abundant natural material. Therefore, the use of cellulose fibers can suitably address environmental issues and save buried resources, and is also preferable from the viewpoints of stable supply of molding materials and molded articles produced using the same, cost reduction, etc. Furthermore, among various fibers, cellulose fibers have particularly high theoretical strength, and are advantageous from the viewpoint of improving the strength of molded articles.
[0023] Examples of the cellulose fibers include cotton, hemp, rayon, cupra, etc. As the cellulose fibers, virgin pulp may be used, or waste paper, old cloth, etc. may be reused.
[0024] Cellulosic fibers are generally composed mainly of cellulose, but may contain components other than cellulose, such as hemicellulose and lignin.
[0025] The cellulose fibers used may be those that have been subjected to a treatment such as bleaching.
[0026] The average length of the cellulose fibers is not particularly limited, but is preferably less than 3 mm, more preferably 50 μm or more and less than 500 μm, and even more preferably 100 μm or more and less than 400 μm.
[0027] This tends to improve the stability of shape, strength, etc. of the molded body produced using the molding material. Also, dust generation in the molded body produced using the molding material tends to be more effectively prevented or suppressed. In particular, even if there is a molding thermal history, dust generation tends to be more effectively suppressed. Also, it may be possible to more effectively prevent the occurrence of undesired irregularities on the surface of the molded body produced using the molding material. The fiber length is determined by a method conforming to ISO 16065-2:2007.
[0028] The average diameter of the cellulose fibers is not particularly limited, but is preferably less than 100 μm, more preferably from 3 μm to less than 50 μm, and even more preferably from 5 μm to less than 20 μm.
[0029] This tends to improve the stability of shape, strength, etc. of the molded article produced using the molding material. In addition, even if there is a molding thermal history, dust generation tends to be suppressed more effectively. In addition, it tends to more effectively prevent the occurrence of undesired irregularities on the surface of the molded article produced using the molding material.
[0030] The average aspect ratio of the cellulose fibers, that is, the average length to the average diameter, is not particularly limited, but is preferably 10 or more and 1,000 or less, and more preferably 15 or more and 100 or less.
[0031] This tends to improve the stability of the shape, strength, etc. of the molded body produced using the molding material. Also, dust generation in the molded body produced using the molding material tends to be more effectively prevented and suppressed. In particular, even if there is a molding heat history, dust generation tends to be more effectively suppressed. Also, it may be possible to more effectively prevent the occurrence of undesired unevenness on the surface of the molded body produced using the molding material.
[0032] The content of cellulose fiber is preferably 2% by mass or more and 40% by mass or less, more preferably 2% by mass or more and 35% by mass or less, even more preferably 2% by mass or more and 30% by mass or less, particularly preferably 2% by mass or more and 25% by mass or less, and more particularly preferably 2% by mass or more and 20% by mass or less, based on the total mass of the molding material. When the content of cellulose fiber is within the above range, the shape stability, strength, etc. of the molded body produced using the molding material tend to be more excellent. In addition, even if there is a molding heat history, dust generation tends to be more excellently suppressed.
[0033] 1.2 Resin The molding material according to the present embodiment contains a resin, and the resin contains a binder and urethane fibers.
[0034] The resin content is preferably 50% by mass or more and 99% by mass or less, more preferably 60% by mass or more and 95% by mass or less, and even more preferably 70% by mass or more and 95% by mass or less, based on the total mass of the molding material. This tends to more effectively suppress dust generation even when there is a molding heat history.
[0035] 1.2.1 Binder By including a binder in the resin in the molding material according to this embodiment, the toughness of the molded body produced using the molding material according to this embodiment can be increased, and the impact resistance of the molded body can be made sufficiently excellent.
[0036] The binder may be any material as long as it can perform the above-mentioned functions, but is usually a resin material.
[0037] Examples of the resin material as a binder, that is, the binder resin, include polyolefins such as polyethylene and polypropylene, and polyesters such as aliphatic polyesters and aromatic polyesters. It is preferable to use one or a combination of two or more selected from these, and more preferably at least one of polyolefins and aliphatic polyesters.
[0038] This makes it possible to improve the affinity between the binder and the urethane, and even if there is a molding thermal history, dust generation tends to be more effectively suppressed.
[0039] Aliphatic polyester is a polyester that does not have an aromatic chemical structure, and all of the constituent monomers do not have an aromatic chemical structure. Examples of aliphatic polyesters include those in which both the polyvalent carboxylic acid component and the polyhydric alcohol component as the constituent monomers have an aliphatic alkylene group. In addition, the aliphatic polyester may be one that is composed of a monomer that has a hydroxyl group and a carboxyl group in the molecule. Examples of aliphatic polyesters that are composed of a monomer that has a hydroxyl group and a carboxyl group in the molecule include polylactic acid.
[0040] When the aliphatic polyester has a chemical structure in which a polyvalent carboxylic acid component having an aliphatic alkylene group and a polyhydric alcohol component having an aliphatic alkylene group are polymerized, the aliphatic polyester preferably has a chemical structure in which an alkylene dicarboxylic acid having an alkylene group with a carbon chain length of 2 to 6 and an alkylene diol having an alkylene group with a carbon chain length of 2 to 8 are condensed. This makes it possible to more effectively exert the function as a binder, and to improve compatibility with urethane, and tends to improve the impact strength and bending strength of a molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be more effectively suppressed.
[0041] The carbon chain length of the alkylene group of the alkylene dicarboxylic acid is preferably 2 to 6, more preferably 2 to 5, and even more preferably 2 to 4. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0042] The alkylene group of the alkylene dicarboxylic acid may have a branched structure, but is preferably linear. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0043] Examples of the alkylene dicarboxylic acid include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. It is preferable to use one or more selected from these in combination.
[0044] The carbon chain length of the alkylene group of the alkylene diol is preferably 2 to 8, more preferably 2 to 6, and even more preferably 3 to 5. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0045] The alkylene group of the alkylene diol may have a branched structure, but is preferably linear. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0046] Examples of the alkylene diol include 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, and 1,8-octanediol. It is preferable to use one or a combination of two or more selected from these.
[0047] Specific examples of aliphatic polyesters containing alkylene dicarboxylic acids and alkylene diols as monomer components that satisfy the above conditions include polybutylene succinate, polybutylene succinate-adipate, polyethylene adipate, etc., and it is preferable to use one or more selected from these in combination. Among these, polybutylene succinate, polybutylene succinate-adipate, and polyethylene adipate are more preferable.
[0048] These materials are biodegradable and can more effectively reduce the environmental impact of molded products. In addition, these materials are relatively inexpensive and can be easily and stably obtained. Therefore, they are advantageous from the viewpoints of stable supply of molding materials and molded products, cost reduction, etc.
[0049] The content of the binder is preferably 35% by mass or more and 94% by mass or less, more preferably 40% by mass or more and 92% by mass or less, and even more preferably 50% by mass or more and 90% by mass or less, based on the total mass of the molding material. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0050] In the molding material according to the present embodiment, when the content of cellulose fiber is XC [mass%] and the content of binder is XB [mass%], it is preferable to satisfy the relationship of 0.01≦XC / XB≦0.60, more preferably to satisfy the relationship of 0.02≦XC / XB≦0.50, and even more preferably to satisfy the relationship of 0.03≦XC / XB≦0.45. This tends to make the impact strength and bending strength of the molded body produced using the molding material better. In addition, even if there is a molding heat history, dust generation tends to be suppressed better.
[0051] 1.2.2 Urethane fiber The resin in the molding material according to this embodiment includes urethane fibers. The urethane fibers are a type of resin fiber, and are fibers made of a material containing urethane. The urethane fibers in the molding material according to this embodiment may be in the form of fibers, or may be in the form of an indefinite shape in which a part or all of the fibers are melted and then solidified. Therefore, the urethane fibers in the molding material may be in the form of fibers, in the form of an indefinite shape, or a mixture thereof. The same applies to resin fibers other than the urethane fibers.
[0052] The urethane fibers are usually melted during the process of producing a molded article using the molding material according to this embodiment, particularly during the heat treatment during molding.
[0053] Urethane is a component that has excellent affinity with both the cellulose fibers and the binder described above.
[0054] Such urethane functions as a compatibilizer when a molded body is produced using the molding material according to this embodiment, improving the compatibility between the cellulose fiber and the binder. This increases the wettability of the binder to the cellulose fiber, and improves the bending strength of the molded body produced using the molding material according to this embodiment. In addition, by including the binder, the heat resistance of the molded body produced using the molding material according to this embodiment can also be improved.
[0055] The urethane constituting the urethane fiber may be any compound in which an amino group and an alcohol group react via a carbonyl group to form a new covalent bond between the nitrogen of the amine and the carbon of the carbonyl group, but is preferably polyurethane.
[0056] When the urethane fiber is a fiber composed of a material containing polyurethane, the number average molecular weight of the polyurethane is preferably 20,000 or more and 300,000 or less, more preferably 30,000 or more and 200,000 or less, and even more preferably 40,000 or more and 150,000 or less.
[0057] This makes it possible to improve the affinity and compatibility of polyurethane with cellulose fibers and binders, and tends to improve the impact strength and flexural strength of molded articles produced using the molding material. In addition, even if the molding material has a thermal history, dust generation tends to be suppressed more effectively.
[0058] The urethane fibers are in a fibrous form in the molding material according to this embodiment, but a portion of them may be in a powdered or molten state, for example.
[0059] The average length of the urethane fiber is not particularly limited, but is preferably less than 3 mm, more preferably 50 μm or more and less than 500 μm, and even more preferably 100 μm or more and less than 400 μm. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0060] The average diameter of the urethane fiber is not particularly limited, but is preferably less than 100 μm, more preferably 3 μm or more and less than 50 μm, and even more preferably 5 μm or more and less than 20 μm. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0061] The average aspect ratio of the urethane fiber, i.e., the average length to the average diameter, is not particularly limited, but is preferably 10 to 1000, more preferably 15 to 100. This tends to improve the impact strength and bending strength of the molded article produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0062] The content of the urethane fiber is preferably 2% by mass or more and 40% by mass or less, more preferably 3% by mass or more and 35% by mass or less, even more preferably 3% by mass or more and 30% by mass or less, particularly preferably 3% by mass or more and 25% by mass or less, and even more particularly preferably 3% by mass or more and 20% by mass or less, based on the total mass of the molding material. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0063] In the molding material according to the present embodiment, when the binder content is XB [mass%] and the urethane fiber content is XU [mass%], it is preferable to satisfy the relationship of 0.01≦XU / XB≦0.60, more preferably to satisfy the relationship of 0.02≦XU / XB≦0.50, and even more preferably to satisfy the relationship of 0.03≦XU / XB≦0.45. This tends to make the impact strength and bending strength of the molded body produced using the molding material better. In addition, even if there is a molding heat history, dust generation tends to be suppressed better.
[0064] When the content of cellulose fiber in the molding material according to this embodiment is XC [mass%] and the content of urethane fiber is XU [mass%], it is preferable to satisfy the relationship of 0.2≦XU / XC≦5.0, more preferably to satisfy the relationship of 0.3≦XU / XC≦3.0, and even more preferably to satisfy the relationship of 0.4≦XU / XC≦2.5. This tends to make the impact strength and bending strength of the molded body produced using the molding material better. In addition, even if there is a molding heat history, dust generation tends to be suppressed better.
[0065] 1.2.3 Other resin fibers The resin in the molding material according to the present embodiment may further contain resin fibers other than urethane fibers (other resin fibers). By containing the other resin fibers, the other resin fibers function as a filler having a wettability similar to that of the binder, which is advantageous in further increasing the strength of the molded body.
[0066] Examples of other resin fibers include polyester fibers, acrylic fibers, nylon fibers, and acetate fibers.
[0067] The average length of the other resin fibers is not particularly limited, but is preferably less than 3 mm, more preferably 50 μm or more and less than 500 μm, and even more preferably 100 μm or more and less than 400 μm. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0068] The average diameter of the other resin fibers is not particularly limited, but is preferably less than 100 μm, more preferably 3 μm or more and less than 50 μm, and even more preferably 5 μm or more and less than 20 μm. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0069] The average aspect ratio of the other resin fibers, i.e., the average length to the average diameter, is not particularly limited, but is preferably 10 to 1000, more preferably 15 to 100. This tends to improve the impact strength and bending strength of the molded article produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0070] The content of the other resin fibers is preferably 1% by mass or more and 30% by mass or less, more preferably 2% by mass or more and 25% by mass or less, and even more preferably 3% by mass or more and 20% by mass or less, based on the total mass of the molding material. This tends to improve the impact strength and bending strength of the molded body produced using the molding material. In addition, even if there is a molding heat history, dust generation tends to be suppressed more effectively.
[0071] In the molding material according to the present embodiment, when the binder content is XB [mass%] and the other resin fiber content is XO [mass%], it is preferable to satisfy the relationship of 0.01≦XO / XB≦0.45, more preferably to satisfy the relationship of 0.02≦XO / XB≦0.36, and even more preferably to satisfy the relationship of 0.03≦XO / XB≦0.30. This tends to make the impact strength and bending strength of the molded body produced using the molding material better. In addition, even if there is a molding heat history, dust generation tends to be suppressed better.
[0072] When the content of cellulose fiber in the molding material according to this embodiment is XC [mass%] and the content of other resin fiber is XO [mass%], it is preferable to satisfy the relationship of 0.1≦XO / XC≦3.8, more preferably to satisfy the relationship of 0.2≦XO / XC≦2.1, and even more preferably to satisfy the relationship of 0.3≦XO / XC≦1.7. This tends to make the impact strength and bending strength of the molded body produced using the molding material better. In addition, even if there is a molding heat history, dust generation tends to be suppressed better.
[0073] 1.2.4 Molecular weight distribution The above-mentioned resin contained in the molding material according to this embodiment has a molecular weight distribution curve measured by a GPC method using chloroform as an eluent, with a local maximum 1 at a weight average molecular weight of 50,000 to 150,000 and a local maximum 2 at a weight average molecular weight of 75,000 to 300,000, and the area value at local maximum 2 is smaller than the area value at local maximum 1. In this way, when the resin has a moderate amount of high molecular weight components, dust generation can be more effectively suppressed even if thermal decomposition of the resin occurs due to the molding heat history.
[0074] The GPC method is a gel permeation chromatography method, and can be measured, for example, by the following procedure. A GPC device (ACQUITY APC, manufactured by Waters) with two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) connected in series is used as the measurement device. The measurement sample (molding material) is dissolved in chloroform as the eluent, filtered through a filter with a pore size of 0.45 μm, and the dissolved components are subjected to GPC analysis to obtain the molecular weight distribution curve of the resin. Here, the column temperature is set to 40°C, and an IR detector is used as the detector. In addition, polystyrene (manufactured by Agilent) is used as the standard sample.
[0075] By using chloroform as the eluent, it is possible to measure resins that are soluble in chloroform, such as polybutylene succinate, polylactic acid, and urethane.
[0076] The peak calculation method can be, for example, as follows. The chromatogram is treated as a linear function, and the position where the slope becomes 0 when differentiated is taken as the peak top. The chromatogram is treated as a linear function, and the position where the slope becomes 0 when differentiated is taken as the peak boundary. The peak is divided vertically from the peak boundary position, and the area value of each peak is calculated. If the peaks are sufficiently separated, the area value may be treated as a single peak. If the two overlapping peaks can be sufficiently distinguished, they may be treated as a shoulder peak, and the base of the smaller peak may be drawn with a straight line to calculate the area value. Furthermore, the area of each peak may be calculated using peak separation software. However, the agreement rate must be 90% or more.
[0077] The resin contained in the molding material according to the present embodiment has a maximum value 1 at a weight average molecular weight of 50,000 to 150,000 in a molecular weight distribution curve obtained by a GPC method using chloroform as an eluent, and the weight average molecular weight is more preferably 50,000 to 130,000, and further preferably 60,000 to 120,000. If the maximum value 1 is within the above range, dust generation tends to be more effectively suppressed even in the case of a molding heat history. In addition, the maximum value 1 is preferably less than the weight average molecular weight at the maximum value 2.
[0078] The resin contained in the molding material according to this embodiment has a maximum value 2 at a weight average molecular weight of 75,000 to 300,000 in a molecular weight distribution curve measured by a GPC method using chloroform as an eluent, and the weight average molecular weight is more preferably 80,000 to 280,000, and further preferably 85,000 to 250,000. When the maximum value 2 is within the above range, dust generation tends to be more effectively suppressed even when there is a molding heat history.
[0079] Here, (weight average molecular weight at maximum value 2) / (weight average molecular weight at maximum value 1) is preferably more than 1.0 and not more than 3.0, more preferably more than 1.0 and not more than 2.5, and even more preferably more than 1.0 and not more than 2.1. In this case, even if there is a molding thermal history, dust generation tends to be more effectively suppressed.
[0080] 1.3 Crosslinking Agent The molding material according to the present embodiment may further contain a crosslinking agent. By containing a crosslinking agent, it is easy to adjust the molecular weight distribution of the resin, and therefore dust generation tends to be more effectively suppressed even when there is a molding heat history.
[0081] The crosslinking agent preferably has a reactive group capable of crosslinking with polyester or urethane. More specifically, the crosslinking agent preferably has a reactive group selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic anhydride, and carboxylic acid. Crosslinking agents having such reactive groups can preferably react with polyester or urethane, and are easy to adjust the molecular weight distribution in the resin, and therefore tend to be able to more effectively suppress dust generation even when there is a molding heat history.
[0082] The crosslinking agent may be a commercially available product, and examples thereof include Metablen P-1901 (manufactured by Mitsubishi Chemical Corporation), Deconal EX-321 (manufactured by Nagase ChemteX Corporation, trimethylolpropane polyglycidyl ether), Deconal EX-211 (manufactured by Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether), Duranate E402-B80B (manufactured by Asahi Kasei Corporation, isocyanate), Carbodilite Elastostab H01 (manufactured by Nisshinbo Chemical Inc.), and MG-670P (manufactured by Riken Vitamin Co., Ltd.).
[0083] The content of the crosslinking agent is preferably 1% by mass or more, more preferably 2% by mass or more, based on the total mass of the molding material. The content of the crosslinking agent is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 6% by mass or less, based on the total mass of the molding material. If the content of the crosslinking agent is within the above range, dust generation tends to be more effectively suppressed even when there is a molding heat history.
[0084] The content of the crosslinking agent is preferably 0.1 parts by mass or more and 20 parts by mass or less, more preferably 0.5 parts by mass or more and 15 parts by mass or less, particularly preferably 1.0 parts by mass or more and 10 parts by mass or less, and more particularly preferably 2.0 parts by mass or more and 8.0 parts by mass or less, when the total content of the resins is taken as 100 parts by mass. When the content of the crosslinking agent is within the above range, dust generation tends to be more effectively suppressed even when there is a molding heat history.
[0085] 1.4 Flame retardants The molding material according to the present embodiment may contain a flame retardant. Known substances can be used as the flame retardant. Examples of the flame retardant include inorganic flame retardants such as antimony compounds, metal hydroxides, nitrogen compounds, and boron compounds, and organic flame retardants such as bromine compounds and phosphorus compounds.
[0086] As the flame retardant, commercially available products may be used, and examples thereof include Rabitol FP-110 (a phosphazene-based flame retardant manufactured by Mitsui Fine Chemicals, Inc.) and Exolit OP1230 (a phosphate-based flame retardant manufactured by Clariant).
[0087] The content of the flame retardant is preferably 5% by mass or more and 30% by mass or less, more preferably 8% by mass or more and 25% by mass or less, and even more preferably 10% by mass or more and 20% by mass or less, based on the total mass of the molding material. When the content of the flame retardant is within the above range, there is a tendency that the flame retardancy of the molded product is improved, and dust generation is more effectively suppressed even when the molded product has a molding heat history.
[0088] The content of the flame retardant is preferably 1 part by mass to 20 parts by mass, more preferably 5 parts by mass to 20 parts by mass, and even more preferably 10 parts by mass to 20 parts by mass, when the total content of the cellulose fiber, the binder, and the urethane fiber is taken as 100 parts by mass. When the content of the flame retardant is within the above range, there is a tendency that the flame retardancy of the molded article is improved, and dust generation can be more effectively suppressed even when the molded article has a thermal molding history.
[0089] 1.5 Other ingredients The molding material according to this embodiment may contain other components, such as a colorant, an insect repellent, an anti-fungal agent, an antioxidant, an ultraviolet absorbing agent, an aggregation inhibitor, and a mold release agent.
[0090] However, the content of other components in the molding material according to this embodiment is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0091] 2. Manufacturing method of molding material Next, a method for producing the molding material according to this embodiment will be described.
[0092] The molding material according to the present embodiment can be produced, for example, by mixing the above-mentioned components. In this case, the components may be mixed at the same time or at different times.
[0093] The molding material according to the present embodiment may be produced, for example, by kneading the above-mentioned components. This effectively exerts the compatibilizing effect of the urethane. For example, a single-screw kneader or a twin-screw kneader can be used to knead the components.
[0094] The strand-like molding material obtained by kneading may be pelletized, for example, using a pelletizer of the strand type or watering hot cut type to form a pellet-like molding material.
[0095] The following method may also be applied as a method for producing a molding material. That is, the kneaded material of the above-mentioned components may be formed into a sheet, and then, for example, cut into a desired shape using a shredder device to obtain a pellet-shaped molding material. The method for forming the kneaded material into a sheet is not particularly limited, but for example, the kneaded material is first deposited in air to form a sheet-shaped deposit, and the deposit is compressed using a calendar device to remove air and increase the density, and then heated in a non-contact manner using a heating furnace, and then hot-pressed using a heat press device. The shape and size of the pellets obtained by cutting are not particularly limited, but for example, they can be approximately rectangular parallelepipeds with a side length of 2 mm to 5 mm.
[0096] The cellulose fibers used in the production of the molding material according to the present embodiment may be those that have been previously subjected to a defibration treatment. In particular, cellulose fiber sources containing cellulose fibers, such as waste paper and old cloth, may be used.
[0097] In addition, when the molding material according to the present embodiment contains other resin fibers, the other resin fibers used in the production of the molding material according to the present embodiment may be those that have been subjected to a defibration treatment in advance. In particular, defibrated resin fiber sources containing other fibers, such as old cloth, may be used.
[0098] The fiber sources as described above, i.e., cellulose fiber sources, urethane fiber sources, and other fiber sources, may be comminuted before being defibrated.
[0099] The fiber source can be crushed by, for example, cutting into small pieces using a shredder having a crushing blade in an atmosphere such as the air. The shape of the small pieces is, for example, approximately a cube or rectangular parallelepiped with a few mm square.
[0100] The small pieces of the fiber source are defibrated to become unraveled fibers. Defibration here refers to the process of unraveling a plurality of fibers that are united together into individual fibers.
[0101] Defibration can be suitably carried out under dry conditions. The term "dry" as used herein means that the process is carried out in air such as the atmosphere, not in a liquid. For the purpose of preventing static electricity, for example, water or the like may be sprayed onto the fibers. Defibration in a dry state can be suitably carried out, for example, by an air flow.
[0102] The fiber sources may be defibrated separately for each fiber source, or may be defibrated in a state where multiple types of fiber sources are mixed together.
[0103] The fiber source may contain two or more types of fibers, more specifically, two or more types of cellulose fibers, urethane fibers, and other resin fibers. Examples of the fiber source containing two or more types of fibers include blended fibers.
[0104] The fiber source may be defibrated in a state in which it contains components other than fibers, such as binders, flame retardants, and other components.
[0105] 3. Molded body Next, a molded body produced using the molding material according to this embodiment will be described.
[0106] The molded article can be produced using the molding material described above.
[0107] The shape of the molded product is not particularly limited, and may be any shape, such as a sheet, a block, a sphere, or a three-dimensional shape.
[0108] The molded article can be suitably produced, for example, by molding the above-mentioned molding material by various molding methods such as injection molding and press molding while heating it.
[0109] The heating temperature of the molding material during molding is not particularly limited, but is preferably less than 200°C, more preferably 120°C to 190°C, and even more preferably 150°C to 180°C.
[0110] After the above-mentioned molding, post-treatments such as machining, eg grinding and polishing, painting, plating, etc. may be carried out.
[0111] 4. Working Example The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the composition columns of Figures 1 to 3 (Tables 1 to 3), the units of values are parts by mass.
[0112] 4.1 Preparation of molding material According to the compositions in Figures 1 to 3 (Tables 1 to 3), molding materials of the examples and comparative examples were manufactured. Specifically, various components were weighed and fed into a Technovel twin-screw kneader KZW15TW-45MG for kneading. The kneading conditions were a maximum heating temperature of 180°C and an extrusion discharge rate of 1 kg / hr. Next, the mixture was processed into a strand shape and then pelletized into molding materials in a pelletizer.
[0113] For the cellulose fibers (cotton fibers, rayon fibers), urethane fibers, polyester fibers, and acrylic fibers, collected clothing from the market was prepared as the fiber source. This fiber source was shredded in the air using a shredder with coarse-shredding teeth into roughly cubes of a few millimeters on each side, and then defibrated by blowing air currents onto the shredded fibers.
[0114] In addition, the average length of the cellulose fibers contained in the molding material was 1.5 mm, the average diameter of the cellulose fibers was 15 μm, the average length of the urethane fibers was 1.5 mm, the average diameter of the urethane fibers was 50 μm, and the number average molecular weight of the polyurethane that constituted the urethane fibers was 60,000.
[0115] The weight average molecular weight of the molding material obtained above was measured by the GPC method. Specifically, a GPC device (ACQUITY APC, manufactured by Waters) with two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) connected in series was used as the measuring device. The measurement sample (molding material) was dissolved in chloroform as an eluent, filtered through a filter with a pore size of 0.45 μm, and the dissolved components were subjected to GPC analysis to obtain a molecular weight distribution curve of the resin. Here, the column temperature was set to 40° C., an IR detector was used as the detector, and polystyrene (manufactured by Agilent) was used as the standard sample. The peak calculation method was performed as described above.
[0116] The descriptions in Figures 1 to 3 (Tables 1 to 3) are supplemented as follows. <binder> Polypropylene (Prime Polymer, H700) Polyethylene (Prime Polymer, 2208J) Polylactic acid (Unitika, Terramac TE-2000) Polybutylene succinate (Mitsubishi Chemical Corporation, Bio PBS FZ71PB) <Crosslinking Agent> Crosslinking agent 1 (Metabrene P-1901, manufactured by Mitsubishi Chemical Corporation) Crosslinking agent 2 (Deconal EX-321, Nagase ChemteX Corporation, trimethylolpropane polyglycidyl ether) Crosslinking agent 3 (Deconal EX-211, manufactured by Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether) Crosslinking agent 4 (Duranate E402-B80B, Asahi Kasei Corporation, isocyanate) Crosslinking agent 5 (Carbodilite Elastostab H01, manufactured by Nisshinbo Chemical Co., Ltd.) Crosslinking agent 6 (MG-670P, manufactured by Riken Vitamin Co., Ltd.) <Elastomer material> Aronkasei, ES-A60NX
[0117] 4.2 Manufacturing of molded bodies The molding materials of each Example and Comparative Example were injection molded using an injection molding machine (THX40-5V, manufactured by Nissei Plastics Co., Ltd.) to produce molded bodies for Charpy impact strength evaluation, bending modulus evaluation, and dust number evaluation, which will be described later. The heating temperature of the molding material during injection molding was 180°C. The molded body for Charpy impact strength evaluation was a rectangular plate-shaped molded body with a long side of 80 mm ± 2 mm, a short side of 4.0 mm ± 0.2 mm, and a thickness of 10.0 mm ± 0.2 mm, and the molded body for bending modulus evaluation and dust number evaluation was a rectangular plate-shaped molded body with a long side of 80 mm ± 2 mm, a short side of 10.0 mm ± 0.2 mm, and a thickness of 4.0 mm ± 0.2 mm.
[0118] Here, in the molding history of Figures 1 to 3 (Tables 1 to 3), "repellet once" means that the above-mentioned molding process was re-pelletized and molding was carried out again in the same manner as above, and "first time" means that molding was carried out only once without re-pelletization. Also, in the crosslinking agent addition step of Figures 1 to 3 (Tables 1 to 3), "repellet" means that the above-mentioned molding process was added when the material was re-pelletized, and "first time" means that the material was added only when the raw materials were mixed. In this way, molded bodies for evaluation in each Example and Comparative Example were obtained.
[0119] 4.3 Evaluation Test 4.3.1 Charpy impact strength The Charpy impact strength of each of the molded bodies for Charpy impact strength evaluation obtained above was measured in accordance with ISO 179 (JIS K7111) using an Impact Tester IT manufactured by Toyo Seiki Seisakusho Co., Ltd. In measuring the Charpy impact strength, the hammer weight was 4J (WR2.14N / m), the lifting angle was 150°, the notch remaining width was 8.0mm±0.2mm, and the notch angle was 45°.
[0120] 4.3.2 Flexural modulus The flexural modulus of each of the molded articles for evaluating the flexural modulus obtained above was measured in accordance with ISO 178 (JIS K7171) using an Instron 68TM-30. In measuring the flexural modulus, the support distance was set to 64 mm.
[0121] 4.3.3 Number of particles generated The above-mentioned Charpy impact strength test was repeated 10 times for the molded body obtained above for evaluating the number of particles generated, and the particle amount within a 10 cm radius area around the impact point of the testing machine was measured and compared with the value before the test. Those where the total amount of particles generated was 20% or less of the initial value were evaluated as "Good", and those where the total amount of particles generated exceeded 20% of the initial value were evaluated as "Poor". Note that fragments on the order of mm that exceed the measurement range of the particle counter were excluded, as they are assumed to be in the environment of use of printer heads, sensors, etc.
[0122] 4.3.4 Combined Evaluation For each of the Examples and Comparative Examples, a composite evaluation was made based on the results of the measurements of the Charpy impact strength, the bending modulus, and the number of particles generated, according to the following criteria. (Judgment criteria) A: Dust generation judged as good, Charpy impact strength is 2.5 kJ / m 2 and flexural modulus of 1.5GPa or more B: Dust generation judged as good, Charpy impact strength is 2.5 kJ / m 2 or higher, or flexural modulus of elasticity of 1.5 GPa or higher (excluding the range of A rating above) C: Dust generation judged as good, Charpy impact strength is 2.5 kJ / m 2 and flexural modulus is less than 1.5 GPa D: Dust generation determination × E: Cannot be molded
[0123] 4.4 Evaluation results The evaluation results are shown in Figures 1 to 3 (Tables 1 to 3).
[0124] From the results shown in Figures 1 to 3 (Tables 1 to 3), it was found that the molding materials according to each example, which contain cellulose fibers and a resin, where the resin contains a binder and urethane fibers, and in a molecular weight distribution curve measured by GPC using chloroform as an eluent, the resin has a maximum value 1 at a weight average molecular weight of 50,000 to 150,000 and a maximum value 2 at a weight average molecular weight of 75,000 to 300,000, and the area value at maximum value 2 is smaller than the area value at maximum value 1, can effectively suppress dust generation even when the molding materials have a molding thermal history.
[0125] In contrast, the molding materials according to the comparative examples, which do not satisfy the above-mentioned configuration, were unable to suppress dust generation when there was a molding thermal history. Note that the molding materials according to the reference examples did not contain a fibrous component, so the problem of dust generation did not occur.
[0126] The following can be derived from the above-described embodiment.
[0127] One embodiment of the molding material is A molding material comprising cellulose fibers and a resin, The resin includes a binder and a urethane fiber, The resin has a molecular weight distribution curve measured by a GPC method using chloroform as an eluent, in which a maximum value 1 is present at a weight average molecular weight of 50,000 to 150,000 and a maximum value 2 is present at a weight average molecular weight of 75,000 to 300,000, The area value at the local maximum value 2 is smaller than the area value at the local maximum value 1.
[0128] In one embodiment of the molding material, The molding material may further contain a crosslinking agent.
[0129] In any one of the embodiments of the molding material, The crosslinker may have reactive groups selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic acid anhydride, carboxylic acid.
[0130] In any one of the embodiments of the molding material, The content of the cellulose fibers may be 2% by mass or more and 40% by mass or less with respect to the total mass of the molding material.
[0131] In any one of the embodiments of the molding material, The cellulose fibres may have an average length of less than 3mm.
[0132] In any one of the embodiments of the molding material, The cellulose fibers may have an average diameter of less than 100 μm.
[0133] In any one of the embodiments of the molding material, The content of the binder may be 35% by mass or more and 94% by mass or less with respect to the total mass of the molding material.
[0134] In any one of the embodiments of the molding material, The content of the urethane fibers may be 2% by mass or more and 40% by mass or less with respect to the total mass of the molding material.
[0135] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the present invention includes a configuration that is substantially the same as the configuration described in the embodiment, for example, a configuration that has the same function, method, and result, or a configuration that has the same purpose and effect. The present invention also includes a configuration in which non-essential parts of the configuration described in the embodiment are replaced. The present invention also includes a configuration that has the same action and effect as the configuration described in the embodiment, or a configuration that can achieve the same purpose. The present invention also includes a configuration in which publicly known technology is added to the configuration described in the embodiment.
Claims
1. A molding material comprising cellulose fibers and a resin, The resin includes a binder and a urethane fiber, The resin has a molecular weight distribution curve measured by a GPC method using chloroform as an eluent, in which a maximum value 1 is obtained at a weight average molecular weight of 50,000 to 150,000 and a maximum value 2 is obtained at a weight average molecular weight of 75,000 to 300,000, A molding material, wherein the area value at the maximum value 2 is smaller than the area value at the maximum value 1.
2. The molding material according to claim 1 , further comprising a crosslinking agent.
3. 3. The molding material of claim 2, wherein the crosslinker has reactive groups selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic acid anhydride, and carboxylic acid.
4. The molding material according to claim 1 or 2, wherein the content of the cellulose fibers is 2% by mass or more and 40% by mass or less with respect to the total mass of the molding material.
5. 3. The molding material according to claim 1 or 2, wherein the cellulose fibers have an average length of less than 3 mm.
6. The molding material according to claim 1 or 2, wherein the cellulose fibers have an average diameter of less than 100 μm.
7. The molding material according to claim 1 or 2, wherein the content of the binder is 35% by mass or more and 94% by mass or less with respect to the total mass of the molding material.
8. The molding material according to claim 1 or 2, wherein the content of the urethane fibers is 2% by mass or more and 40% by mass or less with respect to the total mass of the molding material.
Citation Information
Patent Citations
Cellulose fiber reinforced thermoplastic resin molding and method for producing the same
JP7097521B1